Reverse protein engineering of a novel 4‐domain copper nitrite reductase reveals functional regulation by protein–protein interaction. (28th April 2020) - Sasaki, Daisuke; Watanabe, Tatiana F.; Eady, Robert R.; Garratt, Richard C.; Antonyuk, Svetlana V.; Hasnain, S. Samar
Abstract : Cu‐containing nitrite reductases that convert NO2 ‐ to NO are critical enzymes in nitrogen‐based energy metabolism. Among organisms in the order Rhizobiales, we have identified two copies of nirK, one encoding a new class of 4‐domain CuNiR that has both cytochrome and cupredoxin domains fused at the N terminus and the other, a classical 2‐domain CuNiR ( Br 2D NiR). We report the first enzymatic studies of a novel 4‐domain CuNiR from Bradyrhizobium sp. ORS 375 ( Br NiR), its genetically engineered 3‐ and 2‐domain variants, and Br 2D NiR revealing up to ~ 500‐fold difference in catalytic efficiency in comparison with classical 2‐domain CuNiRs. Contrary to the expectation that tethering would enhance electron delivery by restricting the conformational search by having a self‐contained donor–acceptor system, we demonstrate that 4‐domain Br NiR utilizes N‐terminal tethering for downregulating enzymatic activity instead. Both Br 2D NiR and an engineered 2‐domain variant of Br NiR (Δ(Cyt c ‐Cup) Br NiR) have 3 to 5% NiR activity compared to the well‐characterized 2‐domain CuNiRs from Alcaligenes xylosoxidans ( Ax NiR) and Achromobacter cycloclastes ( Ac NiR). Structural comparison of Δ(Cyt c ‐Cup) Br NiR and Br 2D NiR with classical 2‐domain Ax NiR and Ac NiR reveals structural differences of the proton transfer pathway that could be responsible for the lowering of activity. Our study provides insights into unique structural and functional characteristics of naturally occurring 4‐domain CuNiR and its engineered 3‐ and 2‐domain variants. The reverse protein engineering approach utilized here has shed light onto the broader question of the evolution of transient encounter complexes and tethered electron transfer complexes. Enzyme: Copper‐containing nitrite reductase (CuNiR) (EC 1.7.2.1 ). Database: The atomic coordinate and structure factor of Δ(Cyt c‐ Cup) Br NiR and Br 2D NiR have been deposited in the Protein Data Bank (http://www.rcsb.org/ ) under the accession code 6THE and 6THF, respectively. Abstract : We discovered a new class of 4‐domain Cu‐containing nitrite reductase (CuNiR) from Bradyrhizobium sp. ORS 375 that has both cytochrome ( C ytc) and cupredoxin (Cup) domains tethered to catalytic core (Core) domain at the N‐terminus. This article reports the first characterization of this enzyme ( Br NiR) and its domain‐truncated 3‐ and 2‐domain mutants, Δ C ytc Br NiR and Δ( C ytc‐Cup) Br NiR, respectively, in comparison with well‐studied classical 2‐domain CuNiRs from Alcaligenes xylosoxidans and Achromobacter cycloclastes .